THE ROLE OF PHYSICAL ACTIVITY AND DIETARY HABITS IN PREVENTING OBESITY IN ADULTHOOD - Mihaela Jurdana; Ana Petelin; Maša Černelič Bizjak; Mojca Bizjak; Tadeja Jakus; Zala Jenko Pražnikar (ANNALES ZRS, Scientific Publishing House of ZRS Koper, 2013)
Purpose: The paper discusses the evidence linking physical inactivity and dietary habits with obesity. The hypothesis is that low levels of physical activity and sedentary lifestyles favour a positive energy balance, therefore leading to obesity, low grade inflammation and weight gain. Methods:A total of 96 individuals aged 25-49 years were interviewed by questionnaires for physical activity and eating habits. Based on body mass index (BMI) as well as their percentage of fat mass and waist circumference, the participants were divided into either an overweight or normal weight group. Anthropometric parameters, the biochemical variable C-reactive protein (CRP) and life style factors were compared between the groups using both Student's t-test and the Pearson´s correlation test (r) to identify the correlation between BMI and lifestyle factors.  Results: When the BMI was examined in correlation with various lifestyle factors, a statistically significant difference regarding physical activity and physical fitness was found between the studied groups. In the case of dietary habits, a significantly lower number of consumed meals per day and a higher number of consumed units of meat and meat products were found in the overweight group. Furthermore, a statistical positive correlation was found between the number of meat and meat products consumed and general dissatisfaction with both weight and BMI. In contrast, a negative correlation was discovered between BMI and physical activity as well as physical fitness and the numbers of meal per day. Conclusion: The increasing prevalence of physical inactivity seems to be an imperative explanation for increasing obesity and obesity related disorders.